Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1128/aem.01400-10
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic, Microbiological, and Glycoside Hydrolase Diversities within the Extremely Thermophilic, Plant Biomass-Degrading Genus Caldicellulosiruptor

Abstract: Phylogenetic, microbiological, and comparative genomic analyses were used to examine the diversity among members of the genus Caldicellulosiruptor, with an eye toward the capacity of these extremely thermophilic bacteria to degrade the complex carbohydrate content of plant biomass. Seven species from this genus (C. saccharolyticus, C. bescii, C. hydrothermalis, C. owensensis, C. kronotskyensis, C. lactoaceticus, and C. kristjanssonii) were compared on the basis of 16S rRNA gene phylogeny and cross-species DNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
100
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 59 publications
0
100
0
Order By: Relevance
“…Caldicellulosiruptor bescii is one of the few thermophilic bacteria reported to degrade crystalline cellulose (4,59). It is of interest, therefore, to understand the strategy and the enzymes used by this bacterium for this purpose, as the knowledge could be of industrial importance.…”
Section: Discussionmentioning
confidence: 99%
“…Caldicellulosiruptor bescii is one of the few thermophilic bacteria reported to degrade crystalline cellulose (4,59). It is of interest, therefore, to understand the strategy and the enzymes used by this bacterium for this purpose, as the knowledge could be of industrial importance.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation may give rise to more symbiotic relationships during cellulolytic growth at high temperatures. No archaeal cellulases from D. fermentans have been characterized to date but recently secretome and genome analysis showed several GHs coded by the bacterium C. bescii 21 . Given the limited success in finding single hyperthermophiles that can grow on crystalline cellulose, the discovery of hyperthermophilic cellulases may necessitate the broader application of enrichment driven metagenomics.…”
Section: Discussionmentioning
confidence: 99%
“…With optimal growth temperatures ranging from 70 to 78°C, the genus Caldicellulosiruptor contains the most thermophilic microorganisms capable of biological cellulose hydrolysis known. While 16S rRNA phylogeny indicates a very close relationship within the eight species studied thus far (94.8% to 99.4% identity), microbiological analysis indicated that the genus is more physiologically divergent than previously thought (2). Three complete genome sequences are currently available for this genus, those of C. saccharolyticus (19), C. bescii (12), and C. obsidiansis (5), all of which are capable of crystalline cellulose hydrolysis.…”
mentioning
confidence: 99%